(untitled) (Research, Society and Development, 2023)
Objective: The present study aimed to describe a clinical case of hemoglobin C identification during the periodic examination in a sample of a female employee of the Universidade Federal do Paraná (UFPR). Method: In this study, we report the case of a 40-year-old patient who came to the laboratory school of clinical analysis (LEAC) for routine periodic examinations. The patient answered a questionnaire regarding previous diseases and she did not report the presence of trait or recurrent anemia. Results: During the performance of the CBC and reading of the blood extension under light microscopy, codocytes were found to be present in a large portion of the slide. At first, artifactual codocytes were suspected, but hemoglobin electrophoresis was performed and confirmed the presence of the HbC band. In addition, a quantitative analysis by chromatography (CLAE) was performed, where the presence of approximately 40% HbC was found. Discussion: The case report demonstrates the importance of periodic exams and blood extension evaluation in clinical laboratories for the diagnosis of mild clinical situations, such as hemoglobinopathy C in its heterozygous form. In the context of being a school laboratory, all samples are evaluated microscopically thus ensuring that small alterations can be noticed leading to more accurate diagnosis. Conclusion: In summary, despite all the evolution that has occurred in recent years regarding the automation of the hematology laboratory, cases such as this one show that microscopy and consequently well-trained and experienced professionals are still fundamental to ensure that cases such as this are clarified.